Nuptiality in Soviet and post-Soviet Central Asia - Dommaraju, Premchand (2013)
This study analyses nuptiality patterns in three Central Asian countries—Kazakhstan, Kyrgyzstan and Uzbekistan—over two decades preceding and one decade following the dissolution of the Soviet Union, using census and Demographic Health Survey data. Although marriage remained universal through the end of that period, marriage age increased, and for younger cohorts, marriage rates declined considerably. Marriage age began to increase in the years following independence and there are no signs of any reversal. Within these countries marriage rates showed significant variation by educational achievement, and a much smaller variation by rural-urban residence. In Kazakhstan, ethnic differences in marriage age—Russians marrying earlier than the native Kazakhs—began to narrow. During the years of social, political and economic turmoil that preceded and followed independence, marriage rates increased dramatically followed by a steep decline in Kyrgyzstan and Uzbekistan but not in Kazakhstan. Explanations of these trends are proposed based on the literature on demographic adjustments to social crises and the specifics of Central Asia's historico-cultural and socio-economic contexts.